Twelve new species of Guimaraesiella (Phthiraptera: Ischnocera: Philopteridae) from “babblers” (Passeriformes: Leiothrichidae, Pellorneidae, Timaliidae) with a description of a new subgenus and a key to its species - Gustafsson, Daniel R.; Clayton, Dale H.; Bush, Sarah E. (Zootaxa, 2019)
The chewing louse subgenus Cicchinella new subgenus is erected and described for species of Guimaraesiella Eichler, 1949, parasitizing Old World babblers (Leiothrichidae, Pellorneidae, Timaliidae). The subgenus is divided into three species groups based on chaetotaxy, head and genitalia of both sexes. Two species are redescribed: Guimaraesiella (Cicchinella) sehri (Ansari, 1955) from Trochalopteron lineatum lineatum (Vigors, 1831) and T. lineatum setafer (Hodgson, 1836), and Guimaraesiella (Cicchinella) avinus (Ansari, 1956) from Trochalopteron subunicolor subunicolor Blyth, 1843. In addition, 12 new species are described and illustrated: Guimaraesiella (Cicchinella) falcifrons n. sp. from Actinodura cyanouroptera sordidior (Sharpe, 1888); Guimaraesiella (Cicchinella) iuga n. sp. from Alcippe peracensis peracensis Sharpe, 1887; Guimaraesiella (Cicchinella) gombakensis n. sp. from Turdinus abbotti abbotti (Blyth, 1845); Guimaraesiella (Cicchinella) mcgrewi n. sp. from Alcippe morrisonia Swinhoe, 1863; Guimaraesiella (Cicchinella) tenella n. sp. from Cyanoderma ruficeps davidi (Oustalet, 1899); Guimaraesiella (Cicchinella) retusa n. sp. from Trochalopteron milnei sinianum Stresemann, 1930; Guimaraesiella (Cicchinella) philiproundi n. sp. from Trochalopteron melanostigma schistaceum (Deignan, 1938) and Trochalopteron peninsulae Sharpe, 1887; Guimaraesiella (Cicchinella) hannesundinae n. sp. from Heterophasia picaoides wrayi (Ogilvie-Grant, 1910); Guimaraesiella (Cicchinella) pallidobrunneis n. sp. from Heterophasia melanoleuca melanoleuca (Blyth, 1859); Guimaraesiella (Cicchinella) hampuslybecki n. sp. from Heterophasia auricularis (Swinhoe, 1864); Guimaraesiella (Cicchinella) scottvillai n. sp. from Liocichla steerii Swinhoe, 1877 and Guimaraesiella (Cicchinella) ambusta n. sp. from Leiothrix argentauris rubrogularis Kinnear, 1925. A key to identify the species of Cicchinella, and both a checklist and a host-louse list of the species of Cicchinella known from the Old World babblers are provided.